2005
DOI: 10.1017/s0012162205000332
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in autism spectrum disorders: a population-based study

Abstract: A minority of cases of autism has been associated with several different organic conditions, including bioenergetic metabolism deficiency. In a population-based study, we screened associated medical conditions in a group of 120 children with autism (current age range 11y 5mo to 14y 4mo, mean age 12y 11mo [SD 9.6mo], male:female ratio 2.9:1). Children were diagnosed using Diagnostic and Statistical Manual of Mental Disorders criteria, the Autism Diagnostic Interview--Revised, and the Childhood Autism Rating Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
158
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 231 publications
(174 citation statements)
references
References 20 publications
11
158
5
Order By: Relevance
“…Because hyperlactacidemia and increased lactate/pyruvate ratio may be due to one of several inherited metabolic defects of gluconeogenesis, pyruvate oxidation, the Krebs cycle or the respiratory chain, it is possible that multiple genes influence the observed changes in lactate and pyruvate levels, and that genetic heterogeneity underlies mitochondrial dysfunction associated with autism. Supporting this hypothesis is the fact that, even in the limited number of patients with confirmed mitochondrial disease in our study, we find deficiencies in more than one respiratory chain complexes (Oliveira et al, 2005). The findings also do not corroborate the recently described association of autism with the SLC25A12 gene (Ramoz et al, 2004).…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…Because hyperlactacidemia and increased lactate/pyruvate ratio may be due to one of several inherited metabolic defects of gluconeogenesis, pyruvate oxidation, the Krebs cycle or the respiratory chain, it is possible that multiple genes influence the observed changes in lactate and pyruvate levels, and that genetic heterogeneity underlies mitochondrial dysfunction associated with autism. Supporting this hypothesis is the fact that, even in the limited number of patients with confirmed mitochondrial disease in our study, we find deficiencies in more than one respiratory chain complexes (Oliveira et al, 2005). The findings also do not corroborate the recently described association of autism with the SLC25A12 gene (Ramoz et al, 2004).…”
Section: Discussioncontrasting
confidence: 93%
“…Mitochondrial functional studies confirmed the diagnosis of mitochondrial disease in 5 of these patients (7.2%), a surprisingly high frequency in autism. While the mitochondrial and nuclear genomes exert a dual genetic control on the biogenesis and maintenance of mitochondrial function, in our patients mtDNA mutations were not detected, suggesting the involvement of nuclear genes encoding proteins involved in mitochondrial function (Oliveira et al, 2005).…”
Section: Introductioncontrasting
confidence: 54%
See 3 more Smart Citations